Risk factors of hyperuricemia in patients with non-dialytic chronic kidney disease - Li Pei-shu; Wu Rui-xia; Tan Zhi-cheng (Linchuang shenzangbing zazhi)
Objective To explore the prevalence and risk factors of hyperuricemia（HUA）in patients with non-dialytic chronic kidney disease（ND-CKD）.Methods Clinical data were collected for 540 patients with confirmed ND-CKD between January 2015 and December 2019.They were divided into HUA group（n=295）and non-HUA group（n=245）according to the definition of hyperuricemia（male>420 μmol/L,female>360 μmol/L）.Clinical data of two groups were compared.Logistic regression analysis was employed for identifying the risk factors of HUA in ND-CKD patients.Results The prevalence of HUA was 54.6%.And the incidence of HUA in CKD stage 1～5 patients was 31.7%,50.5%,58.7%,64.3% and 76.3%.Multivariate stepwise logistic regression analysis revealed that male（OR=1.583,95%CI 1.018～2.461,P<0.05）,CKD staging（OR=1.501,95%CI 1.230～1.832,P<0.01）,hypertension（OR=1.632,95%CI 1.020～2.611,P<0.05）,body mass index（OR=1.111,95%CI 1.042～1.186,P<0.01）,blood phosphorus（OR=5.947,95%CI 2.589～13.658,P<0.01）and age（OR=0.971,95%CI 0.957～0.985,P<0.01）were the independent risk factors of HUA in ND-CKD patients.Conclusions The incidence of HUA rises gradually with a higher stage of CKD.Paying close attention to the occurrence of HUA in ND-CKD patients and taking early interventions risk factors may delay the progression of disease.